Unequal negotiations : small states in the new global economy - Lewis, Patsy (2005)
Looks at the emerging phenomenon of the free trade agreements between developing and developed countries. Presents a case study of the experience of Caribbean ACP small states in negotiating the Free Trade Area of the Americas with larger partners in North and South America.